Report from the fourth international consensus meeting to harmonize core outcome measures for atopic eczema/dermatitis clinical trials (HOME initiative). (1st July 2016) - Chalmers, J.R.; Simpson, E.; Apfelbacher, C.J.; Thomas, K.S.; von Kobyletzki, L.; Schmitt, J.; Singh, J.A.; Svensson, Å.; Williams, H.C.; Abuabara, K.; Aoki, V.; Ardeleanu, M.; et al.
Summary: This article is a report of the fourth meeting of the Harmonising Outcome Measures for Eczema (HOME) initiative held in Malmö, Sweden on 23–24 April 2015 (HOME IV). The aim of the meeting was to achieve consensus over the preferred outcome instruments for measuring patient‐reported symptoms and quality of life for the HOME core outcome set for atopic eczema (AE). Following presentations, which included data from systematic reviews, consensus discussions were held in a mixture of whole group and small group discussions. Small groups were allocated a priori to ensure representation of different stakeholders and countries. Decisions were voted on using electronic keypads. For the patient‐reported symptoms, the group agreed by vote that itch, sleep loss, dryness, redness/inflamed skin and irritated skin were all considered essential aspects of AE symptoms. Many instruments for capturing patient‐reported symptoms were discussed [including the Patient‐Oriented SCOring Atopic Dermatitis index, Patient‐Oriented Eczema Measure (POEM), Self‐Administered Eczema Area and Severity Index, Itch Severity Scale, Atopic Dermatitis Quickscore and the Nottingham Eczema Severity Score] and, by consensus, POEM was selected as the preferred instrument to measure patient‐reported symptoms. Further work is needed to determine the reliability and measurement error of POEM. Further work is also required to establish the importance of pain/soreness and the importance of collecting information regarding the intensity of symptoms in addition to their frequency. Much of the discussion on quality of life concerned the Dermatology Life Quality Index and Quality of Life Index for Atopic Dermatitis; however, consensus on a preferred instrument for measuring this domain could not be reached. In summary, POEM is recommended as the HOME core outcome instrument for measuring AE symptoms.